Franklin Maxado e a Xilogravura: o artista contemporâneo e a matriz da cultura popular nordestina - Boeira, Luciana Maciel (2008)
Within the Northeastern context, concentrated on some icons of cultural identity through the woodcut technique ande art of one notable “cordelista” poet the present paper consists of a survey and interpretation of the author’s iconographic work with the theme “Cangaço banditry” with emphasis on a critical analysis of its main character – Virgulino Ferreira da Silva, o Lampião. The “corpus” of the research, interpretation cultural and analyses can be found on the woodcut illustrations made by Franklin Maxado. Who reports the “Cangaço” and his most known representative. The final criticism is on a piece of the whole work by Franklin Maxado and, from that, the artist come up to the artist world with a work considered the first northeastern popular culture the woodcut. And then, it was produced the film “A história cavada na Madeira: o Cangaço, por Franklin Maxado”. Starting from the imbrication - from of representation and contemporary artistc expression - this research was outlined in search of cultural symbolic values through woodcut, under Franklin Maxado’s points of view and expressions.